1994
DOI: 10.1080/01635589409514349
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the effect of tamoxifen,cis‐platin, DTIC, and interferon‐α2b on human melanoma cells in culture by a mixture of vitamins

Abstract: The effect of a mixture of vitamins in modifying the efficacy of commonly used drugs in the treatment of human melanoma has not been studied. Vitamin C and d-alpha-tocopheryl succinate (alpha-TS) alone reduced the growth of human melanoma (SK-30) cells in culture, whereas beta-carotene (BC), 13-cis-retinoic acid (RA), or sodium selenite alone was ineffective. RA caused morphological changes, as evidenced by flattening of cells and formation of short cytoplasmic processes. A mixture of four vitamins (vitamin C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 18 publications
1
46
0
1
Order By: Relevance
“…It has been reported that a combination treatment of minocycline with BC or 13-cis-retinoic acid, along with cisplatin, can result in decreased cytotoxicity (40). Furthermore, a mixture of three or four vitamins containing BC showed the potential to enhance the growth-inhibitory effects of cisplatin on melanoma cells (41). In the present study, we demonstrated for the first time that BC can potentiate the cytotoxic effects of cisplatin against NB CSCs.…”
Section: Discussionmentioning
confidence: 49%
“…It has been reported that a combination treatment of minocycline with BC or 13-cis-retinoic acid, along with cisplatin, can result in decreased cytotoxicity (40). Furthermore, a mixture of three or four vitamins containing BC showed the potential to enhance the growth-inhibitory effects of cisplatin on melanoma cells (41). In the present study, we demonstrated for the first time that BC can potentiate the cytotoxic effects of cisplatin against NB CSCs.…”
Section: Discussionmentioning
confidence: 49%
“…␣-TOS enhances the growth-inhibitory effect of several chemotherapeutic agents on cancer cells in culture. For instance, it augments the effects of doxorubicin (Adriamycin; Pfizer, New York, NY) on prostate carcinoma cells (Ripoll et al, 1986); the effects of cisplatin, tamoxifen, and decaprazine on melanoma cells (Prasad et al, 1994) and parotid acinar carcinoma cells (Prasad and Kumar, 1996); and the effects of doxorubicin on leukemia cells (Fariss et al, 1994).…”
Section: Synergism Of Ve Analogs With Other Inducers Of Apoptosismentioning
confidence: 99%
“…Our interest in antioxidants originated from the pre-clinical studies, which showed that pretreatment with antioxidants, such as vitamin C, beta carotene, alpha tocopheryol succinate and retinoic acid, significantly enhanced the growth inhibitory effects of cisplatin, dacarbazine, tamoxifen and several other anticancer agents on human melanoma and parotid carcinoma cells [6,7]. In a study with mice transplanted with adenocarcinoma of the breast, vitamin A (retinyl palmitate) or synthetic beta-carotene in combination with (x)-irradiation or cyclophosphamide increased the cure rate from 0% to over 90% [22].…”
Section: Discussionmentioning
confidence: 99%